1978
DOI: 10.2527/jas1978.471216x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Influence on Growth and Reproduction of Beef Cattle

Abstract: Ninety-six 7-month-old Hereford heifers (two replicates of 48, one year apart) were individually fed for 2 years a basal ration containing .14% phosphorus on an "as fed" basis, which approxiamted 66% NRC recommendations. Forty-eight of the animals were limited to this low phosphorus (P-) diet. The other 48 (P+) received sufficient monosodium phosphate, top dressed on the basal ration, to elevate phosphorus intake to .36% on an "as fed" basis (174% NRC recommendations). The average daily weight gain for all gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
4
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 7 publications
(6 reference statements)
1
23
4
3
Order By: Relevance
“…The NRC (1996) recommendations on P requirements are higher than data from this experiment and other published work (Call et al, 1978;Erickson et al, 1999). Three possible reasons exist for disagreement between experimental data and NRC (1996) recommendations.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The NRC (1996) recommendations on P requirements are higher than data from this experiment and other published work (Call et al, 1978;Erickson et al, 1999). Three possible reasons exist for disagreement between experimental data and NRC (1996) recommendations.…”
Section: Discussioncontrasting
confidence: 54%
“…Dietary P fed to yearlings in that study ranged from 0.14 to 0.34% of diet DM, with individual intakes of 16 to 36 g/d equating to a range of 71 to 162% of NRC recommendations (Erickson et al, 1999). Similarly, Call et al (1978) fed growing heifers 66 or 174% of NRC-predicted requirements for P during a 2-yr study without adverse effects on gain, BW, or reproduction. Few data are available for beef cattle weighing between 250 and 600 kg fed high-energy finishing diets.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the P required for gain of 1.3 kg/d was .25% P, despite the fact that plasma concentrations were similar in cattle fed each treatment. Long et al (1956) fed growing, yearling beef heifers P levels of .07, .11, and .15% of DM and reported linear improvements in intake, gain, and plasma P. However, Call et al (1978) fed growing heifers primarily hay diets at either 66 (10.3 g/d) or 174% (26.1 g/d) of NRC-predicted P requirements (NRC, 1978) for 2 yr and observed no differences between dietary treatments in gain, body weight, intake, or calving performance.…”
Section: Discussionmentioning
confidence: 99%
“…A deficiência de fósforo está associada a uma série de sintomas inespecíficos, como baixo ganho de peso, consumo reduzido, depravação de apetite e falha reprodutiva (UNDERWOOD, 1981). As concentrações de fósforo indicadas para dietas de bovinos de corte foram aparentemente superestimadas em algumas situações (CALL et al, 1978(CALL et al, , 1986LITTLE, 1980;MARGON et al, 1982;e EZEQUIEL et al, 1988). Comparando as recomendações do NATIONAL RESEARCH COUNCIL -NRC de 1984 e 1996, nota-se que os requisitos para mantença foram reduzidos em cerca de 30%, enquanto para ganho de peso foram aumentados (devido à redução do coeficiente de absorção utilizado [0,68 vs 0,85]) na versão mais recente.…”
Section: Introductionunclassified